Renal events in patients receiving neprilysin inhibitors: a systematic review and meta-analysis. Issue 12 (11th January 2022) - Vollmer Barbosa, Clara; Lang, Hannah; Melk, Anette; Schmidt, Bernhard M W
ABSTRACT: Background: While it is well known that angiotensin-converting enzyme inhibitors (ACEi)/angiotensin receptor blockers (ARBs) increase the risk of acute renal failure, the role of neprilysin inhibition (NEPi) is unclear and some physicians are reluctant to prescribe sacubitril/valsartan because of safety concerns. This meta-analysis aimed to examine the risk for renal events, progression of chronic kidney disease (CKD) or progression to dialysis on combined NEPi and ACEi/ARBs compared with ACEi or ARBs. Methods: We performed a systematic meta-analysis including 17 randomized controlled trials (study drug sacubitril/valsartan or omapatrilat), involving a total of 23 569 patients, after searching PubMed, Cochrane, ClinicalTrials.org and Embase for eligible studies. From the included trials, all renal endpoints, including long- and short-term outcomes and hyperkalemia, were extracted. Pooled odds ratios (ORs) were calculated using the DerSimonian and Laird method. The study was registered at PROSPERO. Results: Overall, treatment with sacubitril/valsartan or omapatrilat showed a slightly lower risk of any renal event [OR 0.82 (0.7–0.97)] compared with treatment with an ACEi or ARB alone. Also, there was a decreased risk of severe acute renal events [OR 0.8 (0.69–0.93)] and a decrease in estimated glomerular filtration rate decline [mean difference −0.58 mL/min (−0.83 to −0.33 mL/min)]. There was no difference in chronic renal events [OR 0.92 (0.8–1.05)] or hyperkalemia [OR 1.02 (0.84–1.23)]. Conclusion: NEPi + ACEi/ARBs are safe in terms of renal adverse events. Longer trials focusing on CKD are needed to evaluate the effect of NEPi on decreasing progression of CKD. Graphical Abstract: